1998
DOI: 10.1523/jneurosci.18-13-04842.1998
|View full text |Cite
|
Sign up to set email alerts
|

On the Action of the Anti-Absence Drug Ethosuximide in the Rat and Cat Thalamus

Abstract: The action of ethosuximide (ETX) on Na+, K+, and Ca2+ currents and on tonic and burst-firing patterns was investigated in rat and cat thalamic neurons in vitro by using patch and sharp microelectrode recordings. In thalamocortical (TC) neurons of the rat dorsal lateral geniculate nucleus (LGN), ETX (0.75-1 mM) decreased the noninactivating Na+ current, INaP, by 60% but had no effect on the transient Na+ current. In TC neurons of the rat and cat LGN, the whole-cell transient outward current was not affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(109 citation statements)
references
References 46 publications
4
104
0
1
Order By: Relevance
“…For example, ethosuximide was claimed to reduce a sustained K ϩ current in thalamic neurons, an effect interpreted as a block of a Ca 2ϩ -activated K ϩ current. 154 In addition, pregabalin was reported to open ATP-sensitive K ϩ channels. 155 Lamotrigine, however, was found to reduce the amplitude of A-type K ϩ currents in cultured hippocampal neurons 156 and levetiracetam was reported to inhibit delayed rectifier but not A-type K ϩ currents in isolated hippocampal neurons.…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ethosuximide was claimed to reduce a sustained K ϩ current in thalamic neurons, an effect interpreted as a block of a Ca 2ϩ -activated K ϩ current. 154 In addition, pregabalin was reported to open ATP-sensitive K ϩ channels. 155 Lamotrigine, however, was found to reduce the amplitude of A-type K ϩ currents in cultured hippocampal neurons 156 and levetiracetam was reported to inhibit delayed rectifier but not A-type K ϩ currents in isolated hippocampal neurons.…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%
“…73,154 Nevertheless, the effect on T-type currents is undoubtedly real, because it has been demonstrated in expressed human receptors 74 ; it is probably large enough to block slow oscillatory firing. Microinfusion of ethosuximide into the thalamus is, however, less effective at blocking spikeand-wave discharges than infusion into the somatosensory cortex, suggesting that molecular targets relating to the initiation of spikes in the cortex (e.g., Na ϩ channels, HCN channels) may be more important than thalamic T-type Ca 2ϩ channels.…”
Section: Molecular Targets For the Treatment Of Absence Seizuresmentioning
confidence: 99%
“…8B) quickly (Ͻ30 min), compared with the slower, and more incomplete block by 1 M U-92032. Other cellular actions of ES have been proposed to contribute to the anti-oscillatory effects of succinimides and related compounds, including reductions in Ca 2ϩ -activated K ϩ and persistent Na ϩ currents (Leresche et al 1998). Such effects might alter neuronal excitability in ways independent of LTS bursts.…”
Section: In Support Of a T-channel-dependent Hypothesis Of Intrathalamentioning
confidence: 99%
“…However, Leresche et al (1998) have recently shown that other cellular actions, reductions in persistent Na ϩ currents and/or Ca 2ϩ -dependent K ϩ currents, may play important roles in the anti-oscillatory effects of ES in thalamus. These and other findings have led to some controversy regarding the T-channel-dependent hypothesis of intrathalamic rhythmicity (reviewed in Crunelli and Leresche 2002;Huguenard 2002).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to ESM's mechanism(s) of action, the advanced molecular and neurochemical studies have provided evidence that the drug preferentially binds to the inactivated state of low-threshold T-type Ca 2 þ channels and selectively inhibits pathological firing without any effect on normal neuronal activity (Coulter et al, 1989;Gomora et al, 2001). Moreover, it has been found that ESM decreases the Ca 2 þ -activated K þ current in thalamo-cortical neurons (Coulter et al, 1989) and partially reduces the noninactivating Na þ current (Leresche et al, 1998). All these changes in Na þ , K þ , and Ca 2 þ currents following the ESM administration are responsible for disrupting thalamo-cortical synchronized activity of neurons during spike and wave discharges in vivo (Crunelli and Leresche, 2002).…”
Section: Discussionmentioning
confidence: 99%